2015
DOI: 10.1111/wrr.12272
|View full text |Cite
|
Sign up to set email alerts
|

Importance of defining experimental conditions in a mouse excisional wound model

Abstract: The murine dorsum dermal excisional wound model has been widely utilized with or without splint application. However, variations in experimental methods create challenges for direct comparison of results provided in the literature and for design of new wound healing studies. Here, we investigated the effects of wound location and size, number of wounds, type of adhesive used for splint fixation on wound healing using splinted or unsplinted dorsum excisional full thickness wound models. One or two 6- or 8-mm fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…After closure, the wound continues to contract and this provides the impression of dominant closure by contraction. Our data is consistent with prior published data that indicates a contribution of ∼50% by reepithelialization during the time period of wound closure …”
supporting
confidence: 93%
“…After closure, the wound continues to contract and this provides the impression of dominant closure by contraction. Our data is consistent with prior published data that indicates a contribution of ∼50% by reepithelialization during the time period of wound closure …”
supporting
confidence: 93%
“…This is consistent with a study on vocal fold wound healing,25 which found that astaxanthin upregulates Col1A1 expression. Wound contraction is another important mechanism in the process of wound closure, especially in rodents 26. Astaxanthin probably accelerates wound contraction during the proliferative and maturation phase by enhancing the function of myofibroblasts, the cells that are differentiated from tissue fibroblasts, which play a key role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…This experimental model has been used to study the biological mechanisms involved skin wound healing 1,2 . STRO was applied topically as natural compounds with healing potential can be tested directly in wound bed 18 .…”
Section: ■ Discussionmentioning
confidence: 99%